Sample-Efficient Multi-Task and Multi-Objective Reinforcement Learning by Combining Multiple Behaviors - Alegre, Lucas N.; Bazzan, Ana L. C.; Silva, Bruno C. da (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2026: Anais do XXXIX Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2026.19119, 2026)
One of the main challenges in the field of artificial intelligence, and reinforcement learning (RL) in particular, is the development of generalist and flexible agents capable of solving multiple tasks—each requiring the agent to learn a potentially new, specialized behavior. Tackling this challenge requires agents to learn behaviors that may involve optimizing a single objective, or trading off between multiple conflicting objectives. In this thesis, we study how to design flexible RL agents that can, in a sample-efficient manner, adapt their behavior to solve any given tasks—each of which is defined by multiple (possibly conflicting) objectives. We introduce new multi-policy methods that empower RL agents to (i) carefully learn multiple behaviors, each specialized in a particular task; and (ii) combine previously-learned behaviors to efficiently identify solutions to novel tasks, which, importantly, may require the agent to assign different preferences to each of its new objectives. The methods we introduce have strong theoretical guarantees regarding the optimality of the set of behaviors learned by agents and their capability to solve new tasks in a zero-shot manner, even in the presence of function approximation errors. We evaluate the proposed methods in various challenging multi-task and multi-objective RL problems and show that our algorithms outperform various current state-of-the-art methods in domains with both discrete and continuous state and action spaces.